2017
DOI: 10.1111/cei.12913
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarkers for the assessment of paediatric systemic lupus erythematosus nephritis

Abstract: The discovery of serum biomarkers specific for paediatric lupus nephritis (pLN) will facilitate the non-invasive diagnosis, follow-up and more appropriate use of treatment. The aim of this study was to explore the role of serum high-mobility group box 1 (HMGB1) protein, antibodies against nucleosomes (anti-NCS), complement factor C1q (anti-C1q) and glomerular basement membrane (anti-GBM) in pLN. Serum samples of 42 patients with paediatric systemic lupus erythematosus (pSLE) (22 with pLN and 20 without renal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
2
7
1
Order By: Relevance
“…In particular, we show for the first time the increased levels of HMGB1 in APS patients. Interestingly, we observed this phenomenon not only in secondary APS (elevated levels of HMGB1 during SLE have already been reported) [ 19 , 34 ] but also in primary APS. During pregnancy, proinflammatory stimuli have been associated with higher risk of adverse pregnancy outcomes, such as preterm birth [ 2 , 35 ].…”
Section: Discussionsupporting
confidence: 62%
“…In particular, we show for the first time the increased levels of HMGB1 in APS patients. Interestingly, we observed this phenomenon not only in secondary APS (elevated levels of HMGB1 during SLE have already been reported) [ 19 , 34 ] but also in primary APS. During pregnancy, proinflammatory stimuli have been associated with higher risk of adverse pregnancy outcomes, such as preterm birth [ 2 , 35 ].…”
Section: Discussionsupporting
confidence: 62%
“…The authors explained this by interference of anti‐HMGB1 antibodies during ELISA measurement and that anti‐HMGB1 is associated with low serum HMGB1 . However, the present study and several others used the ELISA technique for HMGB1 measurement and did not demonstrate that finding. Another investigation demonstrated that serum HMGB1 levels by Western blot were similar to those measured by ELISA …”
Section: Discussioncontrasting
confidence: 80%
“…The same was noted in adult SLE patients . ESR and C‐reactive protein, as classic markers of inflammation, are not specific markers of SLE activity . We found no significant correlation between serum HMGB1 and total leukocyte or absolute neutrophil and/or lymphocyte counts HMGB1 is actively secreted from activated immune cells such as macrophages, dendritic cells and monocytes and is passively released from injured or necrotic cells .…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In fact, diagnosis and appropriate treatments may be delayed, due to non-specific findings in the early phases of disease, thus new biomarkers may improve the management of this life-threating syndrome [39][40][41][42]. Although a rigorous process of validation is needed, the use of novel biomarkers in these patients may help physicians, thus improving diagnosis with early recognition and prompt therapy as well as predicting response to treatment and outcome, as suggested in other rheumatic diseases [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%